Collaborative imagination : earning activism through literacy education - Feigenbaum, Paul (Southern Illinois University Press, 2015)
"Processes of fighting unequal citizenship have historically prioritized literacy education, through which people envision universal first-class citizenship and devise practical methods for enacting this vision. In this important volume, literacy scholar Paul Feigenbaum explores how literacy education can facilitate activism in contemporary contexts in which underserved populations often remain consigned to second-class status despite official guarantees of equal citizenship. By conceiving of education as, in part, a process of understanding and grappling with adaptive and activist rhetorics, Feigenbaum explains, educators can direct people's imaginations toward activism without running up against the conceptual problems so many scholars associate with critical pedagogy. Over time, this model of education expands people's imaginations about what it means to be a good citizen, facilitates increased civic participation, and encourages collective destabilization of, rather than adaptation to, the structural inequalities of mainstream civic institutions. Feigenbaum offers detailed analyses of various locations and time periods inside, outside, and across the walls of formal education, including the Citizenship Schools and Freedom Schools rooted in the Civil Rights Movement of the 1950s and 1960s; the Algebra Project, a current practical-literacy network; and the Imagination Federation, a South Florida-based Earth-Literacy network. Considering both the history and the future of community literacy, Collaborative Imagination offers educators a powerful mechanism for promoting activism through their teaching and scholarship, while providing practical ideas for greater civic engagement among students"--